STUDI PENETAPAN KADAR ASAM HUMAT DENGAN METODE GRAVIMETRI DAN SPEKTROFOTOMETRI UV-VIS - Gusfiyesi, Gusfiyesi; Arizon, Arizon; Efendi, Ressa Yuliza (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2023)
The content of humic acid in the soil is important to determine because humic acid plays a very important role in influencing soil fertility, soil and water chemistry. The use of commercial humic acid is one way to improve the condition of degraded soil and minimize the possibility of losing nutrients from organic fertilizer due to leaching or evaporation. The humus extraction process produces commercial humic acid whose content differs according to the region where the humus is sourced. The content of commercial humic acid is determined gravimetrically, but in this study the humic acid content of commercial humic acid was determined by comparing two analytical methods, namely gravimetry and UV-Vis spectrophotometry. In this research, wet extraction of humic acid was carried out using a mixture of 4% Na4P2O7 and 0.1N NaOH. The average value of humic acid content determined using the gravimetric method was 64.9396% and 29.5193% when tested using the UV-Vis spectrophotometric method. Based on the CoA (Certificate of Analysis) the standard value of humic acid is 50%, so it is concluded that for determining humic acid contents by the gravimetric method is better than the UV-Vis spectrophotometric method.